2013
DOI: 10.1016/j.bbamem.2012.11.026
|View full text |Cite
|
Sign up to set email alerts
|

What can naturally occurring mutations tell us about Cav1.x channel function?

Abstract: Voltage-gated Ca2 + channels allow for Ca2 +-dependent intracellular signaling by directly mediating Ca2 + ion influx, by physical coupling to intracellular Ca2 + release channels or functional coupling to other ion channels such as Ca2 + activated potassium channels. L-type Ca2 + channels that comprise the family of Cav1 channels are expressed in many electrically excitable tissues and are characterized by their unique sensitivity to dihydropyridines. In this issue, we summarize genetic defects in L-type Ca2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…P1351R, V1353M and M1369I correspond to P1336R, V1338M and M1354I (NP_001122312, NP_001122311). Orange, malignant hyperthermia susceptibility; Light blue, hypokalemic periodic paralysis type 1; Green, timothy syndrome; Red, primary aldosteronism; Dark blue, congenital stationary blindness; Black dots, familial hemiplegic migraine; A circle with an arrow indicates a gain of function mutation shown by in vitro studies (Pietrobon 2002, Striessnig et al 2010, Azizan et al 2013, Scholl et al 2013, Stockner & Koschak 2013, Fernandes-Rosa et al 2014, Wang et al 2015. regulatory pathway are important for the tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…P1351R, V1353M and M1369I correspond to P1336R, V1338M and M1354I (NP_001122312, NP_001122311). Orange, malignant hyperthermia susceptibility; Light blue, hypokalemic periodic paralysis type 1; Green, timothy syndrome; Red, primary aldosteronism; Dark blue, congenital stationary blindness; Black dots, familial hemiplegic migraine; A circle with an arrow indicates a gain of function mutation shown by in vitro studies (Pietrobon 2002, Striessnig et al 2010, Azizan et al 2013, Scholl et al 2013, Stockner & Koschak 2013, Fernandes-Rosa et al 2014, Wang et al 2015. regulatory pathway are important for the tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…wild-type CACNA1F constructs and examined functionally in mammalian and oocyte expression systems by different groups. These in vitro studies showed that the different types of mutations can lead to changes in channel function by different transcript/ protein amount, by altered voltage dependence or both Hemara-Wahanui et al, 2005;Hoda et al, 2005Hoda et al, , 2006McRory et al, 2004;Stockner and Koschak, 2013). Reduced channel stability that might promote misfolding of Cav.1 channels has been recently indicated as a possible pathogenic mechanism (Burtscher et al, 2014).…”
Section: Molecules Important For Glutamate Releasementioning
confidence: 97%
“…Structural aberrations identified in CSNB2 patients comprise Ca V 1.4 a1-subunit missense or truncation mutations in addition to insertions or deletions, which can be categorized by their functional effects as loss or gain of function or impairment of the CTM (see above) (Stockner and Koschak, 2013). The complete absence of channel function or altered gating properties is expected to eliminate or decrease Ca V 1.4-mediated Ca 2+ entry required for normal photoreceptor signaling.…”
Section: +mentioning
confidence: 99%